Muhammad Haikal Habibillah - Mahmud sanusi, Muhammad haikal habibillah (TEKNOFILE : Jurnal Sistem Informasi, 2023)
Micro, small, and medium enterprises (MSMEs) are businesses run by individuals, groups, small business entities, and households. Kak Iki's food stall is one of the MSMEs in front of MAN SATU INHIL Jl.Pelajar Tembilahan. In the era of globalization as it is today, the development of information technology is accelerating rapidly. It is necessary to have a data analysis that provides information about sales transactions which includes ordering and payment as well as reporting every transaction to MSME owners. The existence of analysis is very important to be applied to the food stalls of kak Iki which is used as the object of research, because the analysis of sales data in the place has not been managed properly so that there are often accidental data errors in terms of service, ordering, payment, and reporting sales and purchase transactions.